Physical Education Teachers’ Experiences in Fitness Testing (British Journal of Multidisciplinary and Advanced Studies, 2024)
Physical fitness evaluation appears to be of low priority to a subset of educators across various sectors in the Philippines. This study explored the experiences of physical education teachers in fitness testing in the Division of Valencia City with the overarching question on the experiences of Physical Education teachers in fitness testing. To answer this question, a case study design was employed.  Participants were chosen using the purposeful sampling method.  Data were gathered through in-depth interviews and focus group discussion.  The data were analyzed using HyperResearch software to determine the codes, categories, and themes. From the participants’ narratives, three themes emerged namely: adhering to prescribed instructional program, instructional obstacles, and coping strategies. The findings also revealed the following categories: setting clear objectives, conduct of warm-up exercises, implementation of relevant innovation, resource constraints, teacher’s pressure and exhaustion, diverse learner’s perception of Physical Education, managing difficulties, resourcefulness, and continuous assessment. Creating a supportive and inclusive environment, aligning testing with educational goals, and addressing challenges through professional development can enhance the overall experience for both teachers and students in terms of fitness testing. Future researchers may conduct a quantitative study among physical education teachers to gain a general perspective about their experiences, challenges, and perceptions regarding fitness testing.